Two „Protracheoniscus” Species (Crustacea, Isopoda, Oniscidea) in Romanian Fauna: Morphology, Ecology and Distribution - TOMESCU, Nicolae; TEODOR, Lucian Alexandru; FERENŢI, Sára; COVACIU-MARCOV, Severus-Daniel (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Our study is dedicated to two Protracheoniscus species from Romania, Protracheoniscus major and Protracheoniscus politus. The specific morphological characters of Protracheoniscus major Dolfuss 1903 and Protracheoniscus politus C. L. Kock 1841 are redescribed. The morphology of the male pleopod 1 in P. major and Protracheoniscus asiaticus Uljanin 1875 are presented comparatively. At Protracheoniscus politus C.L. Koch 1841 the specific morphological characters, the intraspecific morphological variation of some taxonomical characters and some morphological anomalies are detailed. Also, we presented the changes of the male pleopod 1 endopods morphology after the post reproductive moult, the chitinous lobes of the endopods` tip being removed together with the exuvia. The taxonomic confusions emerging from the remove of the chitinous lobes are presented. The phenomenon of the chitinous lobes` remove in the post reproductive moult was not taken into account by them, new isopod subspecies for science being described. The ecology and the geographic distribution are presented in both species.